Petrophysical assessment of the Hammam Faraun, Matulla and Nubia Reservoirs in the Ashrafi Oil Field, Gulf of Suez - Mohammed Amer; Walid M. Mabrouk; Amr M. Eid; Ahmed Metwally (Scientific Reports)
Abstract The Hammam Faraun, Matulla, and Nubia formations in the Ashrafi oil field, in the southern Gulf of Suez, Egypt, are key hydrocarbon reservoirs with significant economic importance. These formations, characterized by their favorable reservoir properties and structural settings, play a crucial role in oil and gas accumulation. Their study provides valuable insights into regional petroleum systems and guides exploration and production activities. The Ashrafi Oil Field is one of the most complex and important areas due to its intricate geological framework, which closely resembles that of the Red Sea. Its proximity to the Red Sea further emphasizes its significance. Therefore, the findings from this study can serve as a valuable analogy for understanding the geology of the Red Sea. This study presents a comprehensive structural interpretation and petrophysical evaluation of the Hammam Faraun, Matulla, and Nubia formations by examining well log data and seismic lines, the research quantifies essential petrophysical parameters that characterize the reservoir properties and hydrocarbon potential of these formations. The Hammam Faraun Member exhibits effective porosity values ranging from 0.15 to 0.25 and water saturation levels between 0.23 and 0.67, indicating a significant capacity for hydrocarbon storage, especially in the northern region where net pay thickness can reach up to 60 ft. The Matulla Formation shows effective porosity values between 0.10 and 0.20, with water saturation levels ranging from 0.31 to 0.41 and net pay thickness varying from 51 to 269 ft, highlighting its substantial hydrocarbon reserves. In contrast, the Nubia Formation, characterized by its uniform sandstone composition, has an effective porosity of approximately 0.18 and a consistent water saturation level of about 0.24, with net pay thicknesses between 72 and 155 ft, marking it as an important target for hydrocarbon exploration. Also, the resulting structural interpretation reveals a series of normal faulted structures, including horsts, half-grabens, and step faults. These faults extend across the area, primarily trending northeast-southwest (clysmic trend), with minor northwest-southeast faults perpendicular to the major faults, creating a complex fault network. Integrating this structures with petrophysical parameters such as shale volume, effective porosity, and hydrocarbon saturation provides critical insights into reservoir quality, informing future exploration and production strategies. The study further underscores the lateral variations in water saturation and net pay thickness across the formations, which are closely linked to facies changes. This thorough analysis enhances our understanding of the geological framework and serves as a vital resource for optimizing hydrocarbon recovery and guiding exploration initiatives in the Ashrafi Oil Field. The findings underline the potential of these formations as significant contributors to the region’s hydrocarbon resources, emphasizing the necessity for ongoing exploration and development efforts. Additionally, the insights gained from this research can facilitate the implementation of advanced recovery techniques, ensuring the efficient utilization of hydrocarbon resources while addressing the challenges associated with reservoir management in the Gulf of Suez region and the Red sea.